2014
DOI: 10.1002/iub.1267
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian nerve globins in search of functions

Abstract: Nerve globins are present in nonvertebrates and vertebrates, the first nerve globin having been recognized in the nerve cord of the polychaete annelid Aphrodite aculeata in 1872. Later, in 2000, the first vertebrate nerve globin, named neuroglobin (Ngb), has been identified in neuronal tissues of humans and mice. Recently, cytoglobin, hemoglobin, and myoglobin have also been reported to be expressed in the mammalian nervous system. The concentration of mammalian nerve globins is 1 lM, with the exception of Ngb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(53 citation statements)
references
References 150 publications
(258 reference statements)
0
53
0
Order By: Relevance
“…However, the discovery of a second ER subtype in 437 1996 partially solved these ambiguities with the evidence that 438 each E2 cognate receptor subtype (i.e., ERa and ERb) could activate 439 divergent signal transduction pathways [32,43]. This discovery 440 unveiled the paradigm that the balance between ERa and ERb 441 levels and/or activities could drive E2-responsive cells to different [4,29,36,46,52,53,62]. Thus, NGB is a pro-472 survival antiapoptotic molecule for brain-derived tissues.…”
Section: Introductionmentioning
confidence: 94%
“…However, the discovery of a second ER subtype in 437 1996 partially solved these ambiguities with the evidence that 438 each E2 cognate receptor subtype (i.e., ERa and ERb) could activate 439 divergent signal transduction pathways [32,43]. This discovery 440 unveiled the paradigm that the balance between ERa and ERb 441 levels and/or activities could drive E2-responsive cells to different [4,29,36,46,52,53,62]. Thus, NGB is a pro-472 survival antiapoptotic molecule for brain-derived tissues.…”
Section: Introductionmentioning
confidence: 94%
“…The suggested electrochemical approach is free from these complications and can be further used for more detailed studies of the affinity of NGB to bind O 2 or other gases in different conditions. Affinity to O 2 that is regulated through the disulfide bond is an intriguing feature of NGB but its role in O 2 supply/storage is unlikely for many reasons (3,4). The role of NGB as a possible NO dioxygenase is more supported because such a function is well known for hemoglobin, myoglobin, and especially for flavohemoglobin (61).…”
Section: Methodsmentioning
confidence: 99%
“…O 2 binding/supply, the metabolism of reactive nitrogen and oxygen species, apoptosis through different pathways, intracellular signaling, and cell protection during hypoxia and ischemia (1)(2)(3)(4)(5)(6). Besides the central and peripheral nervous system and retina, Ngb is also expressed in endocrine tissues, hematopoietic stem cells, the gastrointestinal tract, and cancer cells (7,8).…”
Section: Neuroglobin (Ngb)mentioning
confidence: 99%
“…Although NGB is an O 2 -binding protein, the initial hypothesis that its protective role was to facilitate oxygen diffusion during periods of anoxia [25] has been challenged (see [58,64]) due to the low levels of the protein in the brain (<1 µM) and to the high O 2 binding rate but low O 2 dissociation rate of NGB [65,66,67]. However, although the biophysical properties of NGB are not optimal for oxygen transport, it has been suggested that the protein could actually play this physiological role at least in some district, as, for instance, in the retina [68].…”
Section: Possible Mechanisms Of Ngb Neuroprotectionmentioning
confidence: 99%